2007
DOI: 10.1002/hep.21734
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and hepatic encephalopathy

Abstract: One of the neurological alterations in patients with minimal or overt hepatic encephalopathy is cognitive impairment. This impairment is reproduced in rats with chronic liver failure due to portacaval shunt (PCS). These rats show decreased ability to learn a conditional discrimination task in a Y-maze, likely due to reduced function of the glutamate-nitric oxide (NO)-cyclic guanosine monophosphate (cGMP) pathway in brain. It has been proposed that inflammation exacerbates the neuropsychological alterations ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 18 publications
8
147
0
2
Order By: Relevance
“…19 In an animal model of MHE, Cauli and colleagues demonstrated an improved learning ability following the administration of the NSAID, ibuprofen. 71 This may act by reducing the inducible nitric oxide activity within the cerebral cortex. In chronic liver disease experimental models, portal vein ligated animals have not been found to exhibit microglial activation, however, feeding rats an ammoniumcontaining diet or performing bile duct ligation (BDL) was sufficient to induce microglial activation and neuroinflammation which was reduced by administering ibuprofen.…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Chronmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In an animal model of MHE, Cauli and colleagues demonstrated an improved learning ability following the administration of the NSAID, ibuprofen. 71 This may act by reducing the inducible nitric oxide activity within the cerebral cortex. In chronic liver disease experimental models, portal vein ligated animals have not been found to exhibit microglial activation, however, feeding rats an ammoniumcontaining diet or performing bile duct ligation (BDL) was sufficient to induce microglial activation and neuroinflammation which was reduced by administering ibuprofen.…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Chronmentioning
confidence: 99%
“…103 In a chronic portocaval-shunted rat model, Cauli and colleagues showed that the NSAID ibuprofen restored the ability of the rats to learn the Y-task maze, in addition to normalization of the function of the glutamate-nitric oxide cyclic guanosine monophosphate enzyme pathway in the cerebral cortex. 71 Unfortunately, NSAID drugs can only have a limited role in the treatment of HE in patients with cirrhosis as they have adverse cardiovascular and renal toxicities which impact upon the protective role of prostaglandins in cellular metabolism.…”
Section: Non-steroidal Anti-inflammatoriesmentioning
confidence: 99%
“…This glutamate-NO-cGMP pathway is impaired in cerebellum of rats with chronic hyperammonemia without 13 or with 14 liver failure. Restoring the pathway and cGMP formation with sildenafil, a phosphodiesterase 5 inhibitor, 14 ibuprofen, an anti-inflammatory, 15 or antagonists of GABA A receptors as bicuculline, 16 restore learning in hyperammonemic rats. However, these treatments may have secondary effects in cirrhotic patients and new psychopharmacological agents are necessary.…”
mentioning
confidence: 99%
“…Experimental studies results show that, epithelial cells produce increased amounts of IL-6, IL-8, or fibronectin following ozone exposure and both IL-6 and fibronectin are secreted vectorially [31]. Animal studies suggesting that inflammationassociated alterations may contribute to cognitive impairment in hepatic encephalopathy [32]. Higher levels of TNFα and IL-6 are detectable in the serum of patients with fulminant hepatitis and cirrhosis [33,34] and inflammatory cytokines in patients with infections and liver disease could influence brain function at different levels including the cerebral endothelial cell and Astrocytes [35].…”
Section: Discussionmentioning
confidence: 99%